Importance of the structural integrity of a carbon conjugated mediator for photocatalytic hydrogen generation from water over a CdS–carbon nanotube–MoS2 composite. Issue 93 (3rd November 2016) - Meng-Jung Li, Molly; Mills, Poppy; Fairclough, Simon M.; Robertson, Alex; Peng, Yung-Kang; Warner, Jamie; Nie, Chunyang; Flahaut, Emmanuel; Edman Tsang, Shik Chi
Abstract : CdS quantum dots is shown to promote photocatalytic hydrogen production from water significantly over single-layer MoS2 on double-walled carbon nanotube. Abstract : Incorporation of CdS quantum dots is shown to significantly promote photocatalytic hydrogen production from water over single-layer MoS2 in a remote manner via their dispersions on a carbon nanotube as a nanocomposite: the hydrogen evolution rate is found to be critically dependent on the content and structural integrity of the carbon nanotube such that the double-walled carbon nanotube shows superior H2 production to a single-walled carbon nanotube because the inner carbon tubules survive from the structural damage during functionalization.